Stakeholder Capacity in Collaborative Policy Innovation in Socio-Economic Development of Coastal Area Communities in Border Areas in Nunukan Regency, North Kalimantan Province - Zainal Arifin Paliwang; Jamaluddin Jompa; Muh. Akmal Ibrahim; Mohammad Thahir Haning (Journal La Bisecoman, 2024)
This research aims to analyze stakeholder capacity in collaborative policy innovation in the socio-economic development of coastal communities in border areas in Nunukan Regency, North Kalimantan Province. The stakeholder capacity implemented is based on Emerson et al. (2012) theory. By analyzing capacity based on procedural and institutional arrangements, leadership, knowledge and resources. The type of research used is descriptive qualitative research. The results of the research explain that in the socio-economic development of society, stakeholder capacity focuses on priority programs owned by the government, showing that in its implementation the government and other stakeholders focus on each program they have, namely improving infrastructure supporting inter-regional connectivity, improving the quality of human resources as the subject and object of development. , optimizing the use of regional potential (agriculture, processing industry, economic businesses) to support the regional economy.